A highly sensitive quantitative method of polysialic acid reveals its unique changes in brain aging and neuropsychiatric disorders - Masaya Hane; Ayane Naramura; Kaito Hayakawa; Chikara Abe; Takahiro Nakagawa; Itaru Kushima; Soma Furukawa; Yuki Fukami; Keisuke Ikegami; Kazumasa Saigoh; Susumu Kusunoki; Masahisa Katsuno; et al. (Scientific Reports)
Abstract Polysialic acid (polySia), a glycoepitope critical for neural development and plasticity, remains difficult to quantify owing to its structural complexity. Here, we present a highly sensitive sandwich enzyme-linked immunosorbent assay (ELISA) utilizing novel probes to measure polySia expression. Using this method, we quantified polySia levels in mouse brain samples across various developmental and aging stages. Notable age-related changes were observed, particularly in neuroplastic regions such as the hippocampus and olfactory bulb, where polySia levels increased at 12 months, potentially reflecting resilience mechanisms against brain aging. Elevated polySia levels in blood samples were also detected in both a schizophrenia mouse model and human patients, with a notable male preponderance. In contrast, no significant changes were observed in patients with chronic inflammatory demyelinating polyneuropathy. These findings, enabled by the novel probes, highlight a potential role for polySia in brain aging and neuropsychiatric disorders, offering new insights into developmental and disease mechanisms and supporting its utility as a diagnostic biomarker for brain impairments.